Impact of examination stress on response time in first-year medical students - Dr. Inderjit Singh; Dr. Yogesh Singh; Dr. Bibhava Vikramaditya; Santosh Singh (International Journal of Medical Research and Review, 2020)
Background: Stress has been seen to deteriorate normal physiological functions as well as the psychological functions of the brain. Medical students face a range of enduring normative stressors in the form of academic demands. This brings upon an amount of stress on the students which is related to the examinations and concerns with achieving high grades consequently referred to as academic-related stress. Thus, it becomes crucial to set upon a tool for measuring this stress in order to present methods for overcoming it. In the present study, one such method is evaluated by assessing the reaction time of first-year medical entrants. Material and Methods: The effect of stress on response time in 50 normal healthy medical students of Sawai Man Singh Medical College, Jaipur in the age group of 18 to 21 years was explored in the study. Visual Reaction Time was recorded through the computer program. Results: There was an increase in visual reaction time for the red color in both the sexes during stressful situations as compared to stress-free situations. While a decrease in Visual Reaction Time was seen for green color. A decreased auditory reaction time for both sexes was seen in stressful situations. Conclusion: The results revealed that stress within a limit facilitates positive feedback to Central Nervous System information processing consequently decreasing the reaction time.